Desirable qualities of modern doctorate advisors in the USA: a view through the lenses of candidates, graduates, and academic advisors. Issue 5 (4th May 2018) - Taylor, Rosemarye T.; Vitale, Thomas; Tapoler, Colton; Whaley, Kari
ABSTRACT: Desirable qualities for modern doctorate academic advisors in the USA that provide for successful completion were explored. In this mixed method study, both interview and survey data were collected. Interviews took place with 13 academic advisors and 18 doctoral candidates and graduates. Thirty-eight academic advisors and 151 candidates and graduates in the USA completed the survey. Participants were from 33 states and represented disciplines of physical therapy, nursing, health, education, and business. Findings across academic advisors, doctoral candidates, and graduates indicate that participants preferred structure in the advising process, helpful and timely feedback, regular communication, emotional support during the doctoral research journey, and a professional relationship that transitions from hierarchical to collegial as the candidate moves to completion of the modern doctorate process. Implications for preparation of academic advisors for modern doctorate candidates may be helpful in supporting their successful completion.